Three new species of Phyllocoptinae (Acari: Eriophyidae) from South China - Li, De-Wei; Wang, Guo-Quan; Wei, Sui-Gai (Zootaxa, 2009)
Three new species of eriophyid mites from Longlin and Heng Counties, Guangxi Zhuang Autonomous Region, South China are described and illustrated: Calacarus cinerascens sp. nov. infesting Cipadessa cinerascens (Pellegr.) Hand.Mazz. (Meliaceae); Calacarus smilax sp. nov. infesting Smilax sp. (Liliaceae) and Tetra guangxiensis sp. nov. infesting Derris sp. (Leguminosae).